Atypical DNA methylation, sRNA-size distribution, and female gametogenesis in Utricularia gibba - Cervantes-Pérez, Sergio Alan (2021)
The most studied DNA methylation pathway in plants is the RNA Directed DNA Methylation (RdDM), a conserved mechanism that involves the role of noncoding RNAs to control the expansion of the noncoding genome. Genome-wide DNA methylation levels have been reported to correlate with genome size. However, little is known about the catalog of noncoding RNAs and the impact on DNA methylation in small plant genomes with reduced noncoding regions. Because of the small length of intergenic regions in the compact genome of the carnivorous plant Utricularia gibba, we investigated its repertoire of noncoding RNA and DNA methylation landscape. Here, we report that, compared to other angiosperms, U. gibba has an unusual distribution of small RNAs and reduced global DNA methylation levels. DNA methylation was determined using a novel strategy based on long-read DNA sequencing with the Pacific Bioscience platform and confirmed by whole-genome bisulfite sequencing. Moreover, some key genes involved in the RdDM pathway may not represented by compensatory paralogs or comprise truncated proteins, for example, U. gibba DICER-LIKE 3 (DCL3), encoding a DICER endonuclease that produces 24-nt small-interfering RNAs, has lost key domains required for complete function. Our results unveil that a truncated DCL3 correlates with a decreased proportion of 24-nt small-interfering RNAs, low DNA methylation levels, and developmental abnormalities during female gametogenesis in U. gibba. Alterations in female gametogenesis are reminiscent of RdDM mutant phenotypes in Arabidopsis thaliana. It would be interesting to further study the biological implications of the DCL3 truncation in U. gibba, as it could represent an initial step in the evolution of RdDM pathway in compact genomes.